TINJAUAN ANALISIS GAYA BERAT TERHADAP BENTUKAN STRUKTUR BAWAH PERMUKAAN DI LEMBAR MEDAN, SUMATERA UTARA - D.A Nainggolan (Pusat Survei Geologi, 2007)
Regionally, tectonics of the Medan Quadrangle is occupied by mountainous and back-arc basin zones. Mountainous zone occupies the southwestern of the quadrangles, and is situated in the northwestern part of Kabanjahe, having Bouguer anomaly ranges from -70 to 0 mgals. Zone of back-arc basin occupying more than 50% of the area extends to the east into the Malacca Strait, having Bouguer anomaly ranges from 0 until +20 mgals. The qualitative and quantitative of Bouguer and residual anomalies represent numerous shapes of anticlinal and synclinal structure including faulting system having direction of northwest - southeast.Â Keywords : mountainous, back-arc basin, Malacca Strait, subsurface structure, Bouguer anomaly